Avaliação de concreto asfáltico com ligante modificado por resíduo industrial contendo escória de cobre pós-jateada como agregado pétreo miúdo - Dias, James Monteiro (2022)
The modification of asphalt binders has as function to obtain asphalt concrete for road pavement coating with mechanical and rheological performance compatible to the conventional, adapting them to the requirements of current traffic densities, through insertion of industrials wastes. In this context, the present work is an experimental study carried out in a laboratory bench, with the purpose of evaluating the contributions, from the point of view of mechanical behavior, that the modification of the CAP 50/70 - by wet route, with oily oil sludge of petroleum and tire rubber, in the proportion of 15/85% (mass/mass), respectively – and the partial replacement of the stone aggregate by residues of post-blasted copper slag, can provide asphalt concrete. For this, specimens (CP's) were processed, mechanical tests were performed and the results published in relevant literature were compared and with the limits established in current technical standards. In this context, the present work shows the results of an experimental study, realized in a laboratory bench of processing and characterizing of asphalt concrete with asphalt binder modified by wet way, with oily petroleum sludge and tire rubber in the proportion 15/85% (mass/mass), respectively, containing partial replacement of the stony aggregate by post-blasted copper slag waste. To this end, tests related to adhesiveness, determination of the binder design content, Los Angeles-Cantabro abrasion, Marshall stability, tensile strength by diametric compression (RTCD) and resilience modulus were performed and compared with values established by technical standards. The results of the Marshall and RTCD stability tests of concrete with modified binder, containing post-blasted copper slag as a partial substitute for fine stone aggregate, were equivalent to those of concrete with the same composition of stone aggregate with unmodified binder (variation ±4%). The resilience modulus of concrete with modified binder was 4371 MPa, while the resilience modulus of asphalt concrete with the same stony aggregate composition, processed with the unmodified binder, was 2887 MPa, indicating greater stiffness. However, the results of mechanical tests, in general, showed that the proposed modifications meet the requirements defined by the technical standards of ABNT and DNIT and indicate that industrial waste, under study, can be used in asphalt paving, offering a good solution for mitigating environmental impacts, reducing the demand for landfills and providing reduction in the use of raw materials of exhaustible resources, as asphalt binders, gravels and sands; combining the development of new technologies for road paving engineering.